ANALISIS KINERJA KEUANGAN DAERAH KABUPATEN/KOTA DI PROVINSI KALIMANTAN SELATAN TAHUN ANGGARAN 2013-2017 - GABBY FEBRYANTI SAHARA; MUZDALIFAH MUZDALIFAH (PPJP Universitas Lambung Mangkurat, 2019)
The aim research (1) to know local financial performance with ratio of fiscal decentralization degree, local financial independent, effectiveness of PAD, local finance efficiencey and growth PAD regencies/municipalities in South Borneo province 2013-2017, (2) to know business sector which contributed in PDRB. Technical analysis data is descriptif analysis. The result research showed : by average fiscal decentralization degree ratio 9 regencies still very less and 4 regencies/cities less, 7 regencies low, average local financial independence 4 regencies still very low, 7 regencies low and 2 municipalities enough independence, average effectivene PAD ratio almost all of regencies/municipalities very effective except Banjarmasin municipality are effective, average local financial efficiency ratio 9 regencies/municipalities less effecient and 2 regencies enough efficient, while Banjarbaru municipalities inefficient, growth PAD ratio is positive. Keywords: fiscal decentralization degree ratio, local financial independence ratio, effectiveness of PAD ratio, local financial efficiency ratio, PAD growth ratio.